Optical imaging of mitochondrial redox state in rodent models with 3-iodothyronamine. (February 2014) - Ghanian, Zahra; Maleki, Sepideh; Reiland, Hannah; Bütz, Daniel E; Chiellini, Grazia; Porter, Fariba-Assadi; Ranji, Mahsa
This study used an optical technique to measure the effects of treating low (10 mg/kg) and high (25 mg/kg) doses of 3-iodothyronamine (T1 AM) on the metabolism in the kidney and heart of mice. The ratio of two intrinsic fluorophores in tissue, (NADH/FAD), called the NADH redox ratio (NADH RR), is a marker of the metabolic state of the tissue. A cryofluorescence imaging instrument was used to provide a quantitative assessment of NADH RR in both kidneys and hearts in mice treated with 3-iodothyronamine. We compared those results to corresponding tissues in control mice. In the kidneys of mice treated with a high dose T1 AM, the mean values of the maximum projection of NADH RR were 2.6 ± 0.6 compared to 3.20 ± 0.03 in control mice, indicating a 19% ( ± 0.4) significant increase in oxidative stress (OS) in the high dose-treated kidneys ( P  = 0.047). However, kidneys treated with a low dose of T1 AM showed no difference in NADH RR compared to the kidneys of control mice. Furthermore, low versus high dose treatment of T1 AM showed different responses in the heart than in the kidneys. The mean value of the maximum projection of NADH RR in the heart changed from 3.0 ± 0.3 to 3.2 ± 0.6 for the low dose and the high dose T1 AM-treated mice, respectively, as compared to 2.8 ± 0.7 in control mice. These values correspond to a 9% (±0.5) ( P  = 0.045) and 14% (±0.5) ( P  = 0.008) significant increase in NADH RR in the T1 AM-treated hearts, indicating that the high dose T1 AM-treated tissues have reduced OS compared to the low dose-treated tissues or the control tissues. These results suggest that while T1 AM at a high dose increases oxidative response in kidneys, it has a protective effect in the heart and may exert its effect through alternative pathways at different doses and at tissue specific levels.